Routledge handbook of Indian transnationalism - Sahoo, Ajaya Kumar; Purkayastha, Bandana, 1956- (Routledge handbooks., 2020)
"This book introduces readers to the many dimensions of historical and contemporary Indian transnationalism and the experiences of migrants and workers to reveal the structures of transnationalism and the ways in which Indian origin groups are affected. The concept of crossing borders emerges as an important theme, along with the weaving of life in geographic and web spaces. The authors draw from a variety of archives and intellectual perspectives in order to map the narratives of Indian transnationalism and analyse the interplay of culture and structures within transnational contexts. The topics covered range from the history of transnational networks, activism, identity, gender, politics, labour, policy, performance, literature and more. This collection presents a wide array of issues and debates which will reinvigorate discussions about Indian transnationalism. This book will be an invaluable resource for academicians, researchers, and students interested in studying South Asia in general and the Indian diaspora in particular"--